MEMAHAMI TEOLOGI PAULUS DALAM KITAB KISAH PARA RASUL - Fenius Gulo (Shema: Jurnal Teologi Injili dan Pendidikan Kristen, 2021)
The narrative of the Book of Acts, the repentance and mission of Paul the Apostole is specially told compared to other figures. Even considering the writings of the apostle Paul himself, the story of his repentance is not written as detail as in the Book of Acts. Thus, it can be assumed that Paul's theology in this book can be understood. This research used qualitative method to prove this hypothesis with a hermeneutic approach that put attention to every context and narrative related to the researched topic. Based on the analysis that has been done, it is confirmed that Paul's theology in this book can be understood through the writings of his colleague, Luke, which includes the story of repentance and preaching the Gospel. Paul's mission in proclaiming the gospel of Jesus Christ has represented his theology in Anthropological, Hamartological, Soteriological, Penumatological, Ecclesiological and Eschatological frameworks. Missiology certainly does not stand alone without being tied to all the dimensions that can be constructed. Thus, all of this can be understood from Paul's theology contained in the Book of Acts. Keywords: Theology, Paul, The Book of Acts